Density‐modulated multilayered homo‐junction tungsten oxide anode materials for high‐capacity Li‐ion batteries with long‐term stability. (1st September 2021) - Kim, Jongmin; Jo, Yongcheol; Ahmed, Abu Talha Aqueel; Inamdar, Akbar I.; Cho, Sangeun; Kim, Hyungsang; Im, Hyunsik
Summary: We report an effective strategy generally applicable towards improving Li‐ion battery performance with insulating metal oxide‐based anode materials. We fabricated density‐modulated multilayered homo‐junction tungsten oxide (WO x ) films as anode materials for Li‐ion batteries, in which high‐ and low‐density thin layers were alternately deposited on Cu current collectors using radio frequency magnetron sputtering. The performance of the battery with multilayered WO x was systematically optimized by changing the number of layers and deposition order. A 4‐layer density‐modulated WO x anode with a low density on top WO x layer showed superior performance with a high reversible capacity of 508 mAh g −1 after 200 cycles at a current density of 0.2 A g −1 . Moreover, it provided a reversible capacity of 150 mAh g −1 and good coulombic efficiency of 93.7% after 1000 cycles at a high current density of 2 A g −1 and showed excellent rate capability and cycling stability. The observed outstanding battery performance of the density‐modulated multilayer WO x anode can be attributed to its controlled mass loading, optimized charge‐transfer kinetics, and favourable morphology. Abstract : In this work, we report an effective strategy generally applicable towards improving Li‐ion battery performance with insulating metal oxide‐based anode materials. We fabricate density‐modulated multilayered homo‐junction tungsten oxide (WO x ) films as anode materials for Li‐ion batteries. The performance of the battery with multilayered WO x is systematically optimized by changing the number of layers and deposition order. The optimized anode film provides a reversible capacity of 150 mAh g −1 and good coulombic efficiency of 93.7% after 1000 cycles at a high current density of 2 A g −1 and shows excellent rate capability and cycling stability.